Relationships between topographic factors, soil and plant communities in a dry Afromontane forest patches of Northwestern Ethiopia. - Liyew Birhanu; Tamrat Bekele; Binyam Tesfaw; Sebsebe Demissew (PLoS ONE, 2021)
Plant community types are influenced by topographic factors, the physical and chemical properties of soil. Therefore, the study was carried out to investigate the relationships of soil and topographic factors on the distribution of species and plant community formation of the Dega Damot district in Northwestern Ethiopia. Vegetation and environmental data were collected from 86 plots (900 m2). Agglomerative hierarchical cluster analysis and redundancy analysis (RDA) with R software were used to identify plant communities and analyze the relationship between plant community types and environmental variables. Five plant community types were identified: Erica arborea-Osyris quadripartita, Discopodium penninervium-Echinops pappii, Olea europaea -Scolopia theifolia, Euphorbia abyssinica-Prunus africana, Dodonaea anguistifolia-Acokanthera schimperi. The RDA result showed that the variation of species distribution and plant community formation were significantly related to altitude, organic matter, moisture content, slope, sand, pH, EC, total nitrogen and phosphorus. Our results suggest that the variation of plant communities (Community 1, 2, 3, and 4) were closely related to environmental factors, including altitude, moisture content, OM, slope, sand, pH, EC, soil nitrogen, and phosphorus, among which altitude was the most important one. However, all the measured environmental variables are not correlated to Dodonaea anguistifolia-Acokanthera schimperi community type. Therefore, it can be concluded that some other environmental variables may influence the species composition, which is needed to be further investigated.